Design, fabrication and experimental testing of IIUM free wing unmanned aerial vehicle (IIUM-FWUAV) - Omar, Ashraf Ali E.; Kurban, Adel (INSI, 2011)
In this work, IIUM’s first free wing unmanned aerial vehicle model (IIUM-FWUAV) was designed, fabricated, tested and investigated experimentally. In constructing the aerial vehicle, the initial weight was estimated and the wing size, fuselage size and aerodynamic forces were determined, after which optimization was carried out. The experimental work was conducted in IIUM low speed closed circuit wind tunnel. The effects of angle of attack and Reynolds number were examined and discussed. Foam, fiber glass, carbon fiber, wood, aluminum and steel were the main materials used to build the experimental model. The experimental data is presented in terms of pressure coefficient distribution, flow visualization, lift and drag coefficient. The effect of angle of attack and Reynolds numbers were studied. The experimental results showed that for free wing UAV the distribution of pressure coefficients behaves differently compared to the fixed wing UAV. The results also showed that the use of free wing configuration can delay flow separation.